Pemanfaatan Bottom Ash Sebagai Bahan Substitusi Agregat Halus Terhadap Kekuatan Beton - Agnes Claudia Posedung; Frans Phengkarsa; Desi Sandy (Program Studi Teknik Sipil UKI Paulus-Makassar, 2020)
Bottom ash is the result of coal combustion which can be useful for the use of concrete mix constituents. In this study, bottom ash is used as a substitute for fine aggregate in the manufacture of concrete. Bottom ash has a larger and heavier grain size with a characteristic dark gray color. The purpose of this study was to determine the strength of concrete using bottom ash as a substitute for fine aggregate. The percentage of the use of bottom ash as a substitute for fine aggregate is 0%, 25%, and 35%. The research was conducted at the Laboratory of Material Technology, Paulus University of Indonesia Christianity. The test objects used were 36 cylinders with a diameter of 15 cm and a height of 30 cm. Tests conducted in the form of compressive strength test, split tensile strength test, and modulus of elasticity test with a concrete quality plan of 30 MPa. From the research results, for the compressive strength test results obtained the optimum bottom ash variation at the use of 35% bottom ash with a compressive strength of 33,764 MPa at the age of 28 days, the split tensile strength test obtained the optimum variety of bottom ash at the use of bottom ash 35% with split tensile strength. of 3,253 MPa at the age of 28 days while the highest modulus of elasticity was obtained at the addition of 35% bottom ash which was 27332.0255 Mpa. And the percentage of split tensile strength relationship for bottom ash variation is 0%, 25%, and 35% of 8.007%, 8.983%, and 9.635% of the compressive strength, respectively. This value meets or is by following per under with what is determined, namely the average ranges from 7% to 11% of the compressive strength with an average of around 9%. From the variation of bottom ash, namely 0%, 25%, and 35% in cylindrical specimens, which reaches f'c 30 Mpa is bottom ash with a variation of 35% and can be used as a substitute for fine aggregate.